Investigating facilitators and barriers to the routine provision of HIV PrEP in community pharmacies in London - Marsha Alter; Shivali Lakhani; Aos Alaa; Manisha Karki; Eva Riboli-Sasco; Austen El-Osta (BMC Health Services Research)
Abstract Background The United Kingdom’s (UK) integration of Pre-exposure Prophylaxis (PrEP) into community pharmacies presents an alternative avenue for supporting Human Immunodeficiency Virus (HIV) prevention. Despite its effectiveness, PrEP's accessibility remains hindered by various barriers within community settings. The aim of this study was to explore the perspectives of pharmacy team members regarding the barriers and facilitators to the routine provision of PrEP in community pharmacies in the UK, as well as any recommendations for mitigating these challenges. Methods Exploratory mixed-method cross-sectional study utilising an online survey and semi-structured interviews with community pharmacists and non-pharmacist team members across the North Thames area of London, England. A convenience sample of 110 pharmacy team members participated in the study, including both pharmacists and non-pharmacists. Two pharmacy technicians and eight pharmacists took part in semi-structured interviews. Data collection involved a cross-sectional online survey and semi-structured interviews. The survey collected data such as demographic characteristics, knowledge, and attitudes towards PrEP provision, while interviews explored in-depth perceptions, experiences and recommendations. Results A significant proportion of respondents expressed a lack of confidence and knowledge regarding PrEP, with training identified as a critical need for facilitating PrEP provision. Additionally, the study highlighted the potential of community pharmacies to increase accessibility of PrEP due to their geographical reach and the trust placed in pharmacists. Conclusion The study demonstrates an interest from community pharmacies in London in providing a commissioned PrEP supply service. However, this would need to be in conjunction with training programmes and public health campaigns to equip community pharmacies for effective PrEP provision. Enhancing pharmacists' competencies and raising public awareness could significantly support the current HIV prevention strategies in the UK.